Compact and quiescent circumgalactic medium and Ly α haloes around extremely red quasars - Gillette, Jarred; Lau, Marie Wingyee; Hamann, Fred; Perrotta, Serena; Rupke, David S N; Wylezalek, Dominika; Zakamska, Nadia L; Vayner, Andrey (Monthly notices of the Royal Astronomical Society, 2023)
Red quasars may represent a young stage of galaxy evolution that provide important feedback to their host galaxies. We are studying a population of extremely red quasars (ERQs) with exceptionally fast and powerful outflows, at median redshift z = 2.6. We present Keck/Keck Cosmic Web Imager integral field spectra of 11 ERQs, which have median colour i-W3 = 5.9 mag, median 〈 Lbol 〉 ≈ 5 × 1047 erg s−1, Ly α halo luminosity 〈 Lhalo 〉 = 5 × 1043 erg s−1, and maximum linear size >128 kpc. The ERQ haloes are generally similar to blue quasar haloes, following known trends with Lbol in halo properties. ERQs have halo symmetries similar to Type-I blue quasars, suggesting Type-I spatial orientations. ERQ 〈 Lhalo 〉 is ∼2-dex below blue quasars, which is marginal due to scatter, but consistent with obscuration lowering photon escape fractions. ERQ haloes tend to have more compact and circularly symmetric inner regions than blue quasars, with median exponential scale lengths ∼9 kpc, compared with ∼16 kpc for blue quasars. When we include the central regions not available in blue quasar studies (due to point spread function problems), the true median ERQ halo scale length is just ∼6 kpc. ERQ haloes are kinematically quiet, with median velocity dispersion 293 km s−1, consistent with expected virial speeds. Overall, we find no evidence for feedback on circumgalactic scales, and the current episode of quasar activity (perhaps due to long outflow travel times) has not been around long enough to affect the circumgalactic medium. We confirm the narrow Ly α-emission spikes found in ERQ aperture spectra are halo features, and are useful for systemic redshifts and measuring outflow speeds in other features.
Veröffentlicht: 26. September 2023
Online veröffentlicht: 26. September 2023
Gesehen am 04.01.2024